LLM-Inspired Offline Reranking for Financial Search: Query Rewriting, Hybrid Retrieval, and Listwise Relevance Ranking on FiQA - Siquan Meng; Jing Chen; Isa Zheng (University of Science and Computer Technology, 2026)
Financial search has high practical value because investors and retail users often ask natural-language questions whose wording differs from relevant financial passages. This paper evaluates a multi-stage retrieval pipeline on FiQA, a financial question-answering retrieval collection in BEIR. The systems include BM25, Dense LSA, BM25-LSA hybrid retrieval, reciprocal-rank fusion, a compact linear reranker, fixed pointwise and listwise relevance rubrics inspired by LLM reranking, query rewriting, and the proposed query rewriting plus hybrid retrieval plus listwise reranking pipeline. The evaluation used the full 57,638-document FiQA corpus, 6,648 available queries, and the 648-query BEIR FiQA test qrels with 1,706 binary relevance judgments. BM25 was the best-performing system, with nDCG@10 = 0.2285, MAP = 0.1863, MRR = 0.2994, and Recall@100 = 0.5207. The proposed full pipeline underperformed BM25. The listwise rubric ranked second on nDCG@10 (0.2228) and improved over the pointwise rubric, suggesting that candidate-list normalization can be useful in this setting. The rubric rerankers are fixed local scoring rules, so these results should be read as an evaluation of LLM-inspired ranking logic rather than as a benchmark of an actual prompt-based LLM reranker. Dense LSA retrieval alone was weak (nDCG@10 = 0.0287), which shows the limitation of a conservative non-neural dense baseline in financial semantic matching. Query rewriting reduced average effectiveness. The findings recommend strong lexical baselines, conservative rewrite gating, and careful evaluation before adopting prompt-based or model-based LLM rerankers in financial search.